ANALISIS PENGARUH DPK, NPF, SWBI DAN SURAT BERHARGA PASAR UANG SYARIAH TERHADAP PENYALURAN PEMBIAYAAN PERBANKAN SYARIAH DI INDONESIA (Periode 2010-2014) - Agustinar Agustinar (Journal Analytica Islamica, 2016)
This research aims to test empirically, (1) How the influence of Depositor Funds, NPF, Wadiah Islamic Certificate of Bank Indonesia and Islamic Financial Markets Securities towards financing distribution at Islamic Banking in Indonesia, (2) What is the most powerful factor influencing toward financing distribution at Islamic Banking in Indonesia? This research took time series data during 2010-2014. To analyze the data was used OLS (Ordinary Least Square) method with multiple linear regression estimation model based on results of data processing by using Eviews program. The research’s results showed that R2 amount is 0.9979 with means that independent variables can explain the dependent variable about 99.79% and 0.21% described by other variables outside of the model. While F-count more than F-table (F-count 51.53 > F-table 2.54), it indicates that all of the independent variables that were used in this analysis, Depositor Funds (DPK), Non Performing Financing (NPF), Wadiah Islamic Certificate of Bank Indonesia (SWBI) and Securities of Islamic Money Markets were simultaneous significantly influential towards financing distribution at Islamic banking in Indonesia. Depositor Funds variable had positive and significant influence towards Islamic banking’s financing distribution and it was most powerful factor influencing towards financing distribution at Islamic banking in Indonesia.